Symptoms Related to Decreased Food Intake in Patients with Cancer of the Digestive System Served by a Home Care Program - Araújo, Évelyn de Sousa (2012)
Introduction: Among gactors associated with malnutrition in cancer, the symptoms related to food intake may contribute significantly to the poor nutritional status. Objective: To assess the prevalence of symptoms related to decreased food intake and its association with tumor location of patients with digestive tract cancer, hospitalized by a Home Care Program for Interdisciplinary Oncology treatment. Method: This is a descriptive study that used secondary data from an Interdisciplinary Oncology Home Care Program. The study included all patients treated for Nutrition, diagnosed with cancer of the digestive tract admitted between February 2006 and February 2011.We analyzed their demographic, clinical and nutritional data. Results: Of the 102 patients studied, whose average age was 61 ±14.1 years old, 100% were regarded with some degree of malnutrition. Bowel cancer was the most predominant in both sexes, followed by cancer of the esophagus. The most prevalent symptoms corresponded to xerostomia (75.5%), early satiety (74.5%), pain (60.8%) and anorexia (53.9%). The prevalence of dysphagia in patients with tumor of the esophagus was approximately four times greater when compared to patients with other tumors of the digestive system (p<0.01 IC 95% 2.35 – 6.48). Conclusion: Xerostomia, early satiety, pain, and anorexia may have contributed to lower food intake, which increases the nutritional status of these patients. Through this knowledge nutritional strategies can be developed to prevent or improve the condition.